The Future of Energy: Exploring Renewable and Non-Renewable Resources - Ahmed, Rashed; Tamim, Md. Tanzimur Rahman (Balai Publikasi Indonesia, 2025)
This comprehensive article delves into the evolving energy landscape, contrasting renewable and non-renewable resources to highlight the global transition toward sustainable energy systems. It underscores the pivotal role of renewable energy sources, such as solar, wind, hydroelectric, and geothermal, as viable solutions to combat climate change and reduce greenhouse gas emissions. The discussion delves into the operational methodologies, tools, and innovations underpinning energy systems, from advanced solar photovoltaics and wind turbines to efficient hydropower and geothermal technologies. Key challenges, such as intermittency, infrastructure costs, and the geographic limitations of renewables, are critically examined alongside the role of non-renewables in current energy mixes. The article also addresses the environmental and societal dimensions, emphasizing ethical guidelines, equity in energy access, and the inclusion of local communities in decision-making. Through a mixed-method research approach, including literature reviews, site visits, and expert interviews, the study offers a nuanced understanding of energy systems. It highlights the importance of integrating sustainable practices and ethical considerations in energy transitions while advocating for technological innovation and international collaboration. The article concludes by emphasizing the critical need for a balanced, multi-faceted strategy to ensure energy security, environmental sustainability, and equitable access for future generations. This research offers a nuanced evaluation of renewable and non-renewable systems. It proposes strategic pathways for integrating diverse energy resources to achieve a balanced, resilient, and sustainable energy future. The study underscores the imperative for international collaboration, technological innovation, and policy advancements to navigate the complexities of this transition, ensuring environmental stewardship and socio-economic benefits for all.